2002
DOI: 10.1271/bbb.66.613
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression of a Rat Fatty Acid Elongase Involved in the Biosynthesis of C18 Fatty Acids

Abstract: A major part of the palmitic acid (C16:0) generated by fatty acid synthase is converted into stearic acid (C18:0) via carbon chain elongation. Here, we describe the cloning and expression of a rat hepatic enzyme, rELO2, responsible for the elongation of C16:0, presumably at the condensing reaction. Heterologous expression experiments in a yeast, Saccharomyces cerevisiae, demonstrated the elongation activity of rELO2 on C16:0 and to a lesser extent, C18:0 and fatty acids with low desaturation degree. This was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 25 publications
6
55
1
Order By: Relevance
“…An abundant amount of Elovl2 mRNA in testis suggested that ELOVL2 elongates PUFAs [8]. This was subsequently demonstrated in mouse [10], human [29] and rat [30,31] orthologs, and in this study (Fig. 1C).…”
Section: Discussionsupporting
confidence: 80%
“…An abundant amount of Elovl2 mRNA in testis suggested that ELOVL2 elongates PUFAs [8]. This was subsequently demonstrated in mouse [10], human [29] and rat [30,31] orthologs, and in this study (Fig. 1C).…”
Section: Discussionsupporting
confidence: 80%
“…The zebrafish enzyme also had substantial C 20 PUFA elongase activity, converting some 46% and 26% of 20:5n-3 and 20:4n-6, respectively, to the respective C 22 products. This is similar to human (ELOVL5) and rat elongases (rELO1), which also have high activity on 20:5n-3 and 20:4n-6 (Leonard et al, 2000b: Inagaki et al, 2002, but in contrast to the elongases of M. alpina and C. elegans which show virtually no activity towards C 20 PUFA (Parker-Barnes et al, 2000;Beaudoin et al, 2000). However, in contrast to the previously reported human and rat elongases described above, the zebrafish elongase also displayed the capacity to elongate C 22 PUFA, converting about 5% of 22:5n-3 to 24:5n-3 in the recombinant yeast system studied.…”
Section: Discussionsupporting
confidence: 58%
“…Functional characterisation has previously been reported for PUFA elongases of nematode (C. elegans), fungus, (M. alpina), rat and human with all four enzymes being predominantly active on C 18 PUFA (Beaudoin et al, 2000;Leonard et al, 2000b;Parker-Barnes et al, 2000;Inagaki et al 2002). This was also the case with zebrafish elongase, the enzyme achieving 90% conversion of 18:4n-3 substrate and 60% of 18:3n-6.…”
Section: Discussionmentioning
confidence: 78%
“…Nearly all the other cloned and functionally characterised elongases from fish reported so far show sequences and functionality similar to mammalian ELOVL5 elongases (Hastings et al, 2005;Agaba et al, 2004Agaba et al, , 2005. The fish Elovl5s have a wider substrate specificity than mammalian ELOVL5s, which elongate predominantly C18 and, to a lesser extent, C20 fatty acids but not C22, whereas most fish Elovl5-like elongases can also elongate 22:5n-3 to 24:5n-3, albeit at a very low level (Leonard et al, 2000;Inagaki et al, 2002;Agaba et al, 2005). Thus, theoretically only this one Elovl5-like elongase might be required for the production of DHA from 18:3n-3 in freshwater fish and, in marine fish, this one elongase would be all that is required to perform both the elongations of EPA necessary for the production of DHA.…”
Section: Discussionmentioning
confidence: 98%